Endotracheal metastasis of colon cancer on FDG PET/CT - BOZKURTLAR, EMİNE; FİLİZOĞLU, NUH; ÖZGÜVEN, SALİH; ERDİL, TANJU YUSUF; ÖNEŞ, TUNÇ (WILEY, 2021)
Although tracheal involvement of lung cancer is frequently seen, endotracheal metastasis of colon cancer is a rare entity. Since endotracheal lesion gives no symptom until tracheal lumen nearly occluded, the diagnosis of endotracheal metastasis could be challenging. F-18 fluorodeoxyglucose positron emission tomography/computed tomography may be crucial to detect this unusal distant metastasis of colon cancer. Herein, we report FDG avid endotracheal lesion that was confirmed as metastasis from colon cancer in 56-year-old female patient.
Keywords: FDG PET; CT; colon cancer; endotracheal; metastasis; TUMORS